The Influence of Social Media Exposure on Adolescent Reproductive Health Practices: Evidence from Indonesian Vocational Students - Lestari, Devi Intan; Ningrum, Ema Wahyu; Safitri, Maya (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Adolescents often grapple with poor reproductive health behaviors due to limited literacy and access to relevant health information, despite the potential of social media as an information source. This study aimed to analyze the association between social media access and adolescent reproductive health behaviors. Employing a quantitative, cross-sectional design, we utilized proportionate random sampling to recruit 290 tenth and eleventh-grade vocational high school students from SMK Tujuh Lima 1 Purwokerto and SMK Ma'arif NU 2 Ajibarang in Banyumas Regency, Indonesia. Data were collected via an online Google Form questionnaire, which demonstrated satisfactory validity (Pearson r=0.334) and reliability (Cronbach's alpha =0.750) for social media access. The majority of respondents were 16 years old (49%), female (60%), and primarily accessed reproductive health information through electronic media (22%). Interestingly, while most reported limited social media access (54%), a large proportion exhibited good reproductive health behaviors (91%). A weak but statistically significant association was found between social media access and reproductive health behaviors (p=0.001, r=0.188). These findings suggest that despite varying levels of social media access, other factors might be more influential in shaping adolescent reproductive health behaviors. We recommend strengthening reproductive health education through engaging and relevant social media content to better leverage its potential as an informative platform for adolescents.